Pengaruh Harga dan Promosi Terhadap Keputusan Pembelian Ceruty Baby Doll pada Opa Gala Textile, Tanah Abang, Jakarta Selatan - Khuzaifah Mohammad Harqom; Syamruddin Syamruddin (Ilmu Sosial, Ekonomi, dan Humaniora, 2025)
The aim of this research is to determine the effect of price and promotion on the purchase decision of Ceruty Baby Doll product at Opa Gala Textile in Jakarta, both partially and simultaneously. This type of research is a type of quantitative research. The population in this research is all Opa Gala Textile customers on 2023 year. The total sample for this research was 75 customers and used a simple random sampling technique. The data collection technique uses a questionnaire method. Data analysis uses the classical assumption test, simple linear regression test, multiple linear regression test, correlation coefficient test, coefficient of determination test, as well as the t test and F test using SPSS version 25 tools. The results of this study show that price (X₁) has an effect positive and significant on purchase decision (Y), with a simple linear regression equation Y = 30,068 + 0,346 X₁. The correlation value for the service quality variable is 0,521 (average). The coefficient of determination value is 27,1%. The calculated t value is 5,211 > t table 1,993 with a significance level of  0.000 < 0.05. Promotion (X₂) has a positive and significant effect on purchase decision (Y), with a simple linear regression equation Y=50,326 + 0,290 X₂. The correlation value is 0,321 (low). The coefficient of determination value is 10,3%. The calculated t value is  2,900 > t tabel 1,993 with a significance of 0.000 < 0.05. Price and promotion simultaneously have a positive and significant effect on purchase decision. Multiple linear regression equation Y= 36,989 + 0,333 X₁ – 0,259 X₂. The correlation value is 0,594 (average). The coefficient of determination value is 35,3%. The calculated F value is 19,602  > F table 3.97 with a significance level of 0.000 < 0.05. Abstrak Tujuan penelitian ini adalah untuk mengetahui pengaruh harga dan promosi terhadap keputusan pembelian produk Ceruty Baby Doll pada Opa Gala Textile Jakarta menggunakan   metode   deskriptif   kuantitatif. Analisis data menggunakan uji asumsi klasik, uji regresi linear sederhana, uji regresi linear berganda, uji koefisien korelasi, uji koefisien determinasi, serta uji t dan uji F dengan menggunakan alat bantu SPSS versi 25. Hasil penelitian ini menunjukan bahwa harga (X₁) berpengaruh positif dan signifikan terhadap keputusan pembelian(Y), dengan persamaan regresi linier sederhana Y = 30,068 + 0,346X1. Nilai korelasi variabel harga sebesar 0,521 (sedang). Nilai koefisien determinasi sebesar 27,1%. Nilai t hitung 5,211 > t tabel 1,993 dengan tingkat signifikan 0,000 < 0,05. Promosi (X₂) berpengaruh positif dan signifikan terhadap kepuasan konsumen (Y), dengan persamaan regresi linier sederhana Y = 50,326 + 0,290 X2. Nilai korelasi sebesar 0,321 (rendah). Nilai koefisien determinasi sebesar 10,3%. Nilai t hitung 2,900 > t tabel 1,993 dengan signifikan 0,000 < 0,05. Harga dan promosi secara simultan berpengaruh positif dan signifikan terhadap keputusan pembelian. Persamaan regresi linier berganda Y = 36,989 + 0,333 X1 – 0,259 X2. Nilai korelasi sebesar 0,594 (sedang). Nilai koefisien determinasi sebesar 35,3%. Nilai F hitung 19,602 > F tabel 3,97 dengan tingkat signifikan 0,000 < 0,05. Kata Kunci: harga; promosi; keputusan pembelian